Inorganic filler doped nanocellulose gas separation membrane, preparation method thereof and application of inorganic filler doped nanocellulose gas separation membrane in separation of CO2 and N2
By loading a Y-type molecular sieve modified with divalent metal cations on cellulose nanofibers, an inorganic filler-doped nanocellulose gas separation membrane was prepared, which solved the problem of difficult to take into account both the selectivity and permeability of the inorganic membrane, and achieved efficient and stable separation of CO2 and N2, which was suitable for industrial gas separation and environmental protection.
Patent Information
- Application Number
- CN202510523852.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-07-04
AI Technical Summary
In the prior art, inorganic membranes have problems in terms of gas separation performance that are difficult to take into account both selectivity and permeability. The mixed matrix membrane has a performance degraded due to uneven dispersion of fillers or interface defects, and the polymer membrane is prone to aging and failure in long-term use.
A Y-type molecular sieve modified with cellulose nanofibers as a scaffold and loaded with divalent metal cations is used to enhance CO2 transmission through π-π* complexation, and combined with the sieving effect of the molecular sieve and the dissolution and diffusion mechanism of cellulose, a nanocellulose gas separation membrane doped with inorganic filler was prepared.
It achieves efficient and stable separation of CO2 and N2, reduces energy consumption, has long-term stability and environmental friendliness, and is suitable for industrial gas separation and reduces greenhouse gas emissions.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of natural polymers, and particularly relates to an inorganic filler-doped nanocellulose gas separation membrane, a preparation method thereof, and an application thereof in separating CO2 and N2. Background Art
[0002] Automobile exhaust emissions and the combustion of fossil fuels have accelerated the emission of CO2, causing the greenhouse effect, sea-level rise, ocean acidification, and climate-induced mass extinction. To reduce CO2 emissions, various technologies have been proposed, including chemical adsorption, physical adsorption, cryogenic fractionation, and membrane separation. Among them, membrane separation is a relatively emerging separation technology. The membrane separation process is usually a pressure-driven process, without the cyclic processes similar to absorption and desorption in the absorption process and adsorption and desorption in the adsorption process. Therefore, the membrane separation method has the advantages of low fixed investment, simple operation, low energy consumption, and small floor area. In the prior art, inorganic membranes (such as molecular sieve membranes) have the characteristic of high selectivity, but their processing performance is poor; although polymer membranes have good processability, they face the problem that it is difficult to balance gas permeability and selectivity; mixed matrix membranes combine the advantages of inorganic fillers and polymer matrices, aiming to optimize performance, but often result in performance degradation due to uneven filler dispersion or interfacial defects. Cellulose is the most abundant sustainable polymer on earth, with many advantages such as low cost, wide availability, and biodegradability. Among them, the membrane prepared from nanocellulose has good mechanical properties, electrical conductivity, and ion selectivity, which is manifested in that the nanocellulose membrane can achieve efficient ion transport in electrolytes with different concentrations. Molecular sieve particles are a kind of porous mineral material, which have excellent adsorption and separation performance due to their nano-pore size, uniform particle size, and mechanical stability, and are widely used in waste gas purification and wastewater treatment. Molecular sieves can be added as fillers to the polymer matrix to improve gas separation performance and endow the composite membrane with pore sieving effect and surface diffusion effect. The entangled network structure of nanocellulose can effectively reduce the non-selective voids in the composite membrane, and the abundant hydroxyl and carboxyl groups provide negative charge points and anchoring positions for the attachment of inorganic fillers, which helps to form good interfacial affinity. The present invention can develop a new type of separation membrane, using molecular sieves modified with divalent metal cations integrated into the nanocellulose matrix to prepare a gas separation membrane, providing a low-cost and environmentally friendly membrane material solution for efficient carbon capture, and having great potential in the application of carbon capture and separation. Summary of the Invention
[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide an inorganic filler-doped nanocellulose gas separation membrane and a preparation method thereof, which are applied to the separation of CO2 and N2 and belong to the field of natural polymers. The present invention is based on using cellulose nanofibers as a scaffold, and loading Y-type molecular sieves modified with divalent metal cations on the cellulose nanofiber scaffold to prepare a composite membrane. The composite membrane prepared by this method utilizes the π-π* complexation of divalent metal cations (such as Zn 2+ 、Co 2+ 、Ni 2+ 、Mg 2+ ) to enhance CO2 transmission, and at the same time makes the sieving effect of the molecular sieve and the dissolution-diffusion mechanism of cellulose cooperate to improve the separation performance, which is applied to the separation of CO2 and N2 to reduce greenhouse gas emissions and improve energy quality, and has an important role in industrial production, environmental protection, etc. The present invention provides a preferred solution for the method of preparing an inorganic filler-doped nanocellulose gas separation membrane, and proposes an efficient and controllable preparation method through research on the preparation process, providing important data support for the efficient preparation, performance optimization and practical application of cellulose composite membranes.
[0004] Technical solution: An inorganic filler-doped nanocellulose gas separation membrane and a preparation method thereof. Preferably, the inorganic filler is a Y-type molecular sieve modified with divalent metal cations. Preferably, the inorganic filler-doped nanocellulose gas separation membrane uses cellulose nanofibers as a scaffold, and a Y-type molecular sieve modified with divalent metal cations is loaded on the cellulose nanofiber scaffold. The preparation method includes the following steps: S1. Prepare a Y-type molecular sieve modified with divalent metal cations: Vacuum dry the NaY molecular sieve powder at 150 °C for 2 days, prepare 40 mL of a divalent metal salt solution with a concentration of 0.1-0.5 mol / L and stir for 1 h; add the dried NaY molecular sieve powder to the divalent metal salt solution respectively and react for 1-2 days. Wash the mixed solution 3 times with 1 L of deionized water under vacuum filtration, and then dry it in an oven at a temperature of 100-200 °C for 3-5 h to obtain Zn 2+ 、Co 2+ 、Ni 2+ 、Mg 2+ -modified ZnY, CoY, NiY, MgY molecular sieve powders; S2. Prepare a cellulose nanofiber CNF dispersion: Dilute the CNF dispersion stock solution with deionized water to 0.01-0.10 wt%, and stir at a low speed of 200-500 rpm for 10-20 h to obtain a CNF dispersion; S3. Mixed divalent metal cation-modified zeolite and CNF dispersion: Add ZnY, CoY, NiY, and MgY into the CNF dispersion at a loading of 5-20 wt% and stir for 10-20 h to form a mixed dispersion, where the mass-volume ratio of the divalent metal cation-modified Y zeolite to the divalent metal salt solution is 0.02-0.25:1 g / mL; then ultrasonically treat the mixed dispersion for 10-20 min, and further treat it with a high-speed disperser at 6000-10000 rpm for 10-30 min to form a well-dispersed mixed dispersion; S4. Vacuum filtration for film formation: Take 10 mL of the well-dispersed mixed dispersion and form a hydrogel filter cake under vacuum filtration. Dry the filter cake in an oven at a temperature of 30-60 °C for 10-20 h to obtain ZnY@CNF, CoY@CNF, NiY@CNF, and MgY@CNF composite membranes with a zeolite loading of 5-20 wt% of ZnY, CoY, NiY, and MgY. Preferably, the divalent metal salt solution in preparation method step S1 is any one or more of zinc salt solution, cobalt salt solution, nickel salt solution, and magnesium salt solution. Furthermore, the zinc salt solution is any one or more of zinc chloride, zinc sulfate, zinc acetate, zinc nitrate, zinc nitrite, zinc phosphate, zinc carbonate, zinc borate, zinc iodide, and zinc bromide; the cobalt salt solution is any one or more of cobalt chloride, cobalt sulfate, cobalt acetate, cobalt nitrate, cobalt carbonate, cobalt iodide, and cobalt bromide; the nickel salt solution is any one or more of nickel chloride, nickel sulfate, nickel nitrate, nickel oxalate, nickel sulfamate, nickel iodide, and nickel bromide; the magnesium salt solution is any one or more of magnesium chloride, magnesium sulfate, magnesium nitrate, magnesium acetate, magnesium bromide, magnesium iodide, and magnesium perchlorate. Furthermore, the concentration of the divalent metal salt solution is 0.1 mol / L; the reaction time is 24 h; the drying temperature is 110 °C, and the drying time is 4 h. Preferably, the concentration of the CNF dispersion in preparation method step S2 is 0.05 wt%; the low-speed stirring rate is 400 rpm; the stirring time is 12 h. Preferably, the stirring time in preparation method step S3 is 12 h; the ultrasonic treatment time is 15 min, the high-speed disperser speed is 8000 rpm, and the treatment time is 10 min. Preferably, the vacuum degree of the vacuum filtration in preparation method step S4 is 100 kPa; the drying temperature is 45 °C, and the drying time is 12 h. Beneficial effects Compared with the prior art, the present invention has the following advantages and positive effects: 1. The inorganic filler-doped nanocellulose gas separation membrane prepared by the present invention has good characteristics, combining high separation performance, long-term stability and environmental friendliness, and has broad application prospects and significant environmental benefits. 2. As a matrix material, nanocellulose has excellent biodegradability and environmental friendliness, meeting the concepts of green chemistry and sustainable development. At the same time, the surface of nanocellulose is rich in hydroxyl groups, providing abundant active sites for functional modification. By introducing divalent metal cations (such as Zn 2+ etc.) to form strong interactions with the hydroxyl groups on the surface of nanocellulose, not only the cross-linking effect between nanocellulose molecular chains is enhanced, but also the generation of interfacial defects is significantly inhibited, thereby improving the structural stability and mechanical strength of the gas separation membrane. This strong interaction also enables the membrane material to maintain stable performance during long-term use, avoiding the problem of performance degradation caused by interfacial defects. 3. The present invention doped inorganic fillers (such as Y-type molecular sieves) with specific pore sizes and surface characteristics into the nanocellulose matrix. The porous structure of the molecular sieve endows it with excellent sieving effect, enabling efficient selective separation according to the size and polarity of gas molecules. At the same time, the dissolution-diffusion mechanism inherent in nanocellulose and the sieving effect of the molecular sieve form a synergistic effect, further enhancing the selectivity and permeability of the gas separation membrane. Especially in the field of CO2 separation, the pore size design of the molecular sieve can preferentially adsorb CO2 molecules, while the dissolution-diffusion mechanism of nanocellulose promotes the rapid transport of CO2 in the membrane, thus realizing the efficient separation of CO2 from other gases (such as N2). This synergistic effect not only improves the separation efficiency but also reduces energy consumption, providing an efficient and energy-saving solution for industrial gas separation. 4. The inorganic filler-doped nanocellulose gas separation membrane prepared by the present invention exhibits excellent stability during long-term use. Due to the introduction of divalent metal cations and the uniform dispersion of the molecular sieve, the membrane material can still maintain stable separation performance under harsh conditions such as high temperature and high pressure, avoiding the problem of easy aging and failure of traditional polymer membrane materials. At the same time, the renewable and environmentally friendly nature of nanocellulose enables the membrane material to degrade naturally after the end of its service life, reducing secondary pollution to the environment. Description of the Drawings Figure 1 is the XRD pattern of NaY molecular sieve and Y-type molecular sieves modified by different divalent metal cations; Figure 2 is the SEM image of NaY molecular sieve and Y-type molecular sieves modified by different divalent metal cations; Figure 3 is the gas permeability diagram of composite membranes of NaY@CNF, ZnY@CNF, CoY@CNF, NiY@CNF, MgY@CNF with different loadings and pure CNF membrane; Figure 4 Gas selectivity performance diagrams of NaY@CNF, ZnY@CNF, CoY@CNF, NiY@CNF, MgY@CNF composite membranes with different proportions of molecular sieves loaded and pure CNF membrane; Figure 5 Gas separation performance diagram of ZnY@CNF composite membrane at different temperatures; Figure 6 Gas separation performance diagram of ZnY@CNF composite membrane at different pressures; Figure 7 XRD diagrams of ZnY@CNF composite membrane, pure CNF membrane, and ZnY molecular sieve; Figure 8 FT-IR diagrams of ZnY@CNF composite membrane, pure CNF membrane, and ZnY molecular sieve; Figure 9 TGA diagrams of ZnY@CNF composite membrane, pure CNF membrane, and ZnY molecular sieve; Figure 10 CO2 adsorption performance diagrams of ZnY@CNF composite membrane and pure CNF membrane at 0 °C and 25 °C; Figure 11 Gas permeability performance diagrams of ZnY@CNF composite membrane and Comparative Example 1 - Comparative Example 8; Figure 12 Gas selectivity performance diagrams of ZnY@CNF composite membrane and Comparative Example 1 - Comparative Example 8. Specific embodiments To further understand the present invention, the preferred embodiments of the present invention will be described below in conjunction with examples. The specific preferred examples are as follows: Example 1 This example is the preparation of ZnY@CNF, a cellulose composite membrane modified with 5 wt% Zn 2+ modified Y-type molecular sieve, including the following steps: S1. Prepare Zn 2+ modified Y-type molecular sieve: Vacuum dry the NaY molecular sieve at 150 °C for 2 days, and prepare 40 mL of zinc nitrate solution with a concentration of 0.1 mol / L, and stir for 1 h; Weigh 1 g of the dried NaY molecular sieve powder and add it to the zinc nitrate solution, and stir for 24 h; The mixed solution is rinsed 3 times with 1 L of deionized water under vacuum filtration, and the obtained molecular sieve is dried in an oven at 110 °C for 4 h to obtain Zn 2+ modified ZnY molecular sieve powder; S2. Prepare cellulose nanofiber CNF dispersion: Dilute 5 mL of CNF dispersion mother liquor with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain CNF dispersion; S3. Mix the ZnY zeolite and CNF dispersion: Add ZnY to the CNF dispersion at a loading of 5 wt%, stir for 12 h, then ultrasonically treat for 15 min, and further treat with a high-speed disperser at 8000 rpm for 10 min to form a mixed dispersion; S4. Vacuum filtration to form a film: Take 10 mL of the well-dispersed mixed dispersion and vacuum filter it under a vacuum of 100 kPa to form a hydrogel cake. The cake is dried in an oven at 45 °C for 12 h to obtain a ZnY@CNF composite film with a ZnY zeolite loading of 5 wt%. Example 2 The difference between Example 2 and Example 1 is the different loading of ZnY. In this example, the loading of ZnY is 10 wt%. Example 3 The difference between Example 3 and Example 1 is the different loading of ZnY. In this example, the loading of ZnY is 15 wt%. Example 4 The difference between Example 4 and Example 1 is the different loading of ZnY. In this example, the loading of ZnY is 20 wt%. Example 5 This example is the preparation of a Co 2+ modified Y-type zeolite cellulose composite film CoY@CNF, including the following steps: S1. Prepare Co 2+ modified Y-type zeolite: Vacuum dry the NaY zeolite at 150 °C for 2 days, and prepare 40 mL of a cobalt nitrate solution with a concentration of 0.1 mol / L, and stir for 1 h; Weigh 1 g of the dried NaY zeolite powder and add it to the cobalt nitrate solution, and stir for 24 h; The mixed solution is rinsed 3 times with 1 L of deionized water under vacuum filtration, and the obtained zeolite is dried in an oven at 110 °C for 4 h to obtain Co 2+ modified CoY zeolite powder; S2. Prepare the cellulose nanofiber CNF dispersion: Dilute 5 mL of the CNF dispersion mother liquor with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain the CNF dispersion; S3. Mix the CoY zeolite and CNF dispersion: Add CoY to the CNF dispersion at a loading of 5 wt%, stir for 12 h, then ultrasonically treat for 15 min, and further treat with a high-speed disperser at 8000 rpm for 10 min to form a mixed dispersion; S4. Vacuum filtration for film formation: Take 10 mL of the well-dispersed mixed dispersion and conduct vacuum filtration under a vacuum degree of 100 kPa to form a hydrogel filter cake. The filter cake is dried in an oven at 45 °C for 12 h to obtain a CoY@CNF composite film with a CoY molecular sieve loading of 5 wt%. Example 6 The difference between Example 6 and Example 5 lies in the different loadings of CoY. In this example, the loading of CoY is 10 wt%. Example 7 The difference between Example 7 and Example 5 lies in the different loadings of CoY. In this example, the loading of CoY is 15 wt%. Example 8 The difference between Example 8 and Example 5 lies in the different loadings of CoY. In this example, the loading of CoY is 20 wt%. Example 9 This example is about the preparation of a modified Y-type molecular sieve cellulose composite film NiY@CNF with a loading of 5 wt% Ni 2+ The preparation of the modified Y-type molecular sieve cellulose composite film NiY@CNF includes the following steps: S1. Prepare Ni 2+ Modified Y-type molecular sieve: Vacuum-dry the NaY molecular sieve at 150 °C for 2 days, and prepare 40 mL of a nickel nitrate solution with a concentration of 0.1 mol / L, and stir for 1 h; Weigh 1 g of the dried NaY molecular sieve powder and add it to the nickel nitrate solution, and stir for 24 h; The mixed solution is rinsed 3 times with 1 L of deionized water under vacuum filtration, and the obtained molecular sieve is dried in an oven at 110 °C for 4 h to obtain Ni 2+ Modified NiY molecular sieve powder; S2. Prepare the cellulose nanofiber CNF dispersion: Dilute 5 mL of the CNF dispersion stock solution with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain the CNF dispersion; S3. Mix the NiY molecular sieve and the CNF dispersion: Add the NiY with a loading of 5 wt% to the CNF dispersion, stir for 12 h, then perform ultrasonic treatment for 15 min, and further process it with a high-speed disperser at 8000 rpm for 10 min to form a mixed dispersion; S4. Vacuum filtration for film formation: Take 10 mL of the well-dispersed mixed dispersion and conduct vacuum filtration under a vacuum degree of 100 kPa to form a hydrogel filter cake. The filter cake is dried in an oven at 45 °C for 12 h to obtain a NiY@CNF composite film with a NiY molecular sieve loading of 5 wt%. Example 10 The difference between Example 10 and Example 9 lies in the different loadings of NiY. In this example, the loading of NiY is 10 wt%. Example 11 Example 11 differs from Example 9 in the loading amount of NiY. In this example, the loading amount of NiY is 15 wt%. Example 12 Example 12 differs from Example 9 in the loading amount of NiY. In this example, the loading amount of NiY is 20 wt%. Example 13 This example is a MgY@CNF composite membrane of Y-type molecular sieve cellulose modified with 5 wt% Mg 2+ The preparation of the modified Y-type molecular sieve cellulose composite membrane MgY@CNF includes the following steps: S1. Prepare Mg 2+ Modified Y-type molecular sieve: Vacuum dry the NaY molecular sieve at 150 °C for 2 days, and prepare 40 mL of magnesium nitrate solution with a concentration of 0.1 mol / L, and stir for 1 h; Weigh 1 g of the dried NaY molecular sieve powder and add it to the magnesium nitrate solution, and stir for 24 h; The mixed solution is rinsed 3 times with 1 L of deionized water under vacuum filtration, and the obtained molecular sieve is dried in an oven at 110 °C for 4 h to obtain Mg 2+ Modified MgY molecular sieve powder; S2. Prepare the cellulose nanofiber CNF dispersion: Dilute 5 mL of the CNF dispersion mother liquor with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain the CNF dispersion; S3. Mix the MgY molecular sieve and the CNF dispersion: Add the MgY with a loading amount of 5 wt% to the CNF dispersion, stir for 12 h, then ultrasonically treat for 15 min, and further treat with a high-speed disperser at 8000 rpm for 10 min to form a mixed dispersion; S4. Vacuum filtration to form a film: Take 10 mL of the well-dispersed mixed dispersion and vacuum filter it under a vacuum degree of 100 kPa to form a hydrogel filter cake. The filter cake is dried in an oven at 45 °C for 12 h to obtain the MgY@CNF composite membrane with a MgY molecular sieve loading amount of 5 wt%. Example 14 Example 14 differs from Example 13 in the loading amount of MgY. In this example, the loading amount of MgY is 10 wt%. Example 15 Example 15 differs from Example 13 in the loading amount of MgY. In this example, the loading amount of MgY is 15 wt%. Example 16 Example 16 differs from Example 13 in the loading amount of MgY. In this example, the loading amount of MgY is 20 wt%. The data of CO2 permeability and CO2 / N2 selectivity of Examples 1 to 16 are listed in Table 1. To further illustrate the technical effects of the present invention, the present invention also sets up comparative examples, which are specifically as follows: Comparative Example 1 The difference between Comparative Example 1 and the optimal sample 15wt% ZnY@CNF in Example 3 is that Comparative Example 1 is a NaY molecular sieve without modification by divalent metal cations. Comparative Example 2 The difference between Comparative Example 2 and the optimal sample 15wt% ZnY@CNF in Example 3 is that Comparative Example 2 is ZnY, which is a Y-type molecular sieve modified by Zn without being compounded with any material, and the preparation method is the same as step S1 of Example 1. 2+ Comparative Example 3 The difference between Comparative Example 3 and the optimal sample 15wt% ZnY@CNF in Example 3 is that Comparative Example 3 is a pure CNF membrane without any molecular sieve loaded, and the preparation method includes the following steps: S1. Prepare a cellulose nanofiber CNF dispersion: Dilute 5 mL of the CNF dispersion mother liquor with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain a CNF dispersion; S2. Vacuum filtration to form a membrane: Take 10 mL of the well-dispersed CNF dispersion and vacuum filter it under a vacuum of 100 kPa to form a hydrogel filter cake, and dry the filter cake in an oven at 45 °C for 12 h to obtain a CNF membrane. Comparative Example 4 The difference between Comparative Example 4 and the optimal sample 15wt% ZnY@CNF in Example 3 is that Comparative Example 4 is a NaY@CNF composite membrane with a molecular sieve loading of 15 wt%, and the CNF membrane is loaded with a molecular sieve NaY without modification by divalent metal cations. The preparation method includes the following steps: S1. Prepare NaY molecular sieve: Dry the NaY molecular sieve in an oven at 110 °C for 4 h; S2. Prepare a cellulose nanofiber CNF dispersion: Dilute 5 mL of the CNF dispersion mother liquor with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain a CNF dispersion; S3. Mix the NaY molecular sieve and the CNF dispersion: Add NaY to the CNF dispersion at a loading of 15 wt%, stir for 12 h, then ultrasonically treat for 15 min, and further treat with a high-speed disperser at 8000 rpm for 10 min to form a mixed dispersion; S4. Vacuum filtration to form a membrane: Take 10 mL of the well-dispersed mixed dispersion and vacuum filter it under a vacuum of 100 kPa to form a hydrogel filter cake, and dry the filter cake in an oven at 45 °C for 12 h to obtain a NaY@CNF composite membrane with a NaY molecular sieve loading of 15 wt%. Comparative Example 5 Comparative Example 5 The difference between Comparative Example 5 and the optimal sample of 15 wt% ZnY@CNF in Example 3 is that Comparative Example 5 is a ZnY@GO composite membrane with a loading amount of 15 wt%. The molecular sieve ZnY modified with divalent metal cations is graphene oxide GO, and the preparation method includes the following steps: S1. Prepare divalent metal cation-modified Y-type molecular sieve: Vacuum-dry NaY molecular sieve at 150 °C for 2 days; Prepare 40 mL of zinc nitrate solution with a concentration of 0.1 mol / L and stir for 1 h; Weigh 1 g of the dried NaY molecular sieve powder and add it to the zinc nitrate solution, and stir for 24 h; The mixed solution is rinsed 3 times with 1 L of deionized water under vacuum filtration, and the obtained molecular sieve is dried in an oven at 110 °C for 4 h to obtain divalent metal cation-modified ZnY molecular sieve powder; S2. Prepare graphene oxide solution: Dilute 5 mL of graphene oxide mother liquor with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain graphene oxide solution; S3. Mix ZnY molecular sieve and graphene oxide solution: Add ZnY to the dispersion at a loading amount of 15 wt%, stir for 12 h, then ultrasonically treat for 15 min, and further treat with a high-speed disperser at 8000 rpm for 10 min to form a mixed solution; S4. Vacuum filtration to form a membrane: Take 10 mL of the well-dispersed mixed solution and vacuum filter it at a vacuum degree of 100 kPa to form a hydrogel cake, and the cake is dried in an oven at 45 °C for 12 h to obtain a ZnY@GO composite membrane with a molecular sieve loading amount of 15 wt%. Comparative Example 6 The difference between Comparative Example 6 and the optimal sample of 15 wt% ZnY@CNF in Example 3 is that Comparative Example 6 is a KY@CNF composite membrane with a molecular sieve loading amount of 15 wt%. The CNF membrane is loaded with monovalent metal ion K + Modified Y-type molecular sieve KY, the preparation method includes the following steps: S1. Prepare monovalent metal cation-modified Y-type molecular sieve: Vacuum-dry NaY molecular sieve at 150 °C for 2 days; Prepare 40 mL of potassium nitrate solution with a concentration of 0.1 mol / L and stir for 1 h; Weigh 1 g of the dried NaY molecular sieve powder and add it to the potassium nitrate solution, and stir for 24 h; The mixed solution is rinsed 3 times with 1 L of deionized water under vacuum filtration, and the obtained molecular sieve is dried in an oven at 110 °C for 4 h to obtain K + Modified KY molecular sieve powder; S2. Prepare cellulose nanofiber CNF dispersion: Dilute 5 mL of CNF dispersion mother liquor with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain CNF dispersion; S3. Mix KY zeolite and CNF dispersion: Add KY to the CNF dispersion at a loading of 15 wt% and stir for 12 h, then ultrasonically treat for 15 min, and further treat with a high-speed disperser at 8000 rpm for 10 min to form a mixed dispersion; S4. Vacuum filtration to form a film: Take 10 mL of the well-dispersed mixed dispersion and vacuum filter it under a vacuum of 100 kPa to form a hydrogel cake. The cake is dried in an oven at 45 °C for 12 h to obtain a KY@CNF composite film with a KY zeolite loading of 15 wt%. Comparative Example 7 The difference between Comparative Example 7 and the optimal sample 15 wt% ZnY@CNF in Example 3 is that Comparative Example 7 is an AlY@CNF composite film with a molecular sieve loading of 15 wt%, and the CNF film is loaded with trivalent metal ion Al 3+ Modified Y-type zeolite AlY, the preparation method includes the following steps: S1. Prepare trivalent metal cation-modified Y-type zeolite: Vacuum dry NaY zeolite at 150 °C for 2 days; Prepare 40 mL of aluminum nitrate solution with a concentration of 0.1 mol / L and stir for 1 h; Weigh 1 g of the dried NaY zeolite powder and add it to the aluminum nitrate solution, stir for 24 h; The mixed solution is rinsed 3 times with 1 L of deionized water under vacuum filtration, and the obtained zeolite is dried in an oven at 110 °C for 4 h to obtain Al 3+ Modified AlY zeolite powder; S2. Prepare cellulose nanofiber CNF dispersion: Dilute 5 mL of the CNF dispersion mother liquor with 95 g of deionized water to 0.05 wt% and stir at a low speed of 400 rpm for 12 h to obtain the CNF dispersion; S3. Mix AlY zeolite and CNF dispersion: Add AlY to the CNF dispersion at a loading of 15 wt% and stir for 12 h, then ultrasonically treat for 15 min, and further treat with a high-speed disperser at 8000 rpm for 10 min to form a mixed dispersion; S4. Vacuum filtration to form a film: Take 10 mL of the well-dispersed mixed dispersion and vacuum filter it under a vacuum of 100 kPa to form a hydrogel cake. The cake is dried in an oven at 45 °C for 12 h to obtain an AlY@CNF composite film with an AlY zeolite loading of 15 wt%. Comparative Example 8 The difference between Comparative Example 8 and the optimal sample 15 wt% ZnY@CNF in Example 3 is that Comparative Example 8 is a ZnX@CNF composite film with a loading of 15 wt%, and the CNF film is loaded with divalent metal cation-modified X-type zeolite ZnX. The preparation method includes the following steps: S1. Prepare divalent metal cation-modified X-type zeolite: Vacuum dry NaX zeolite at 150 °C for 2 days; Prepare 40 mL of zinc nitrate solution with a concentration of 0.1 mol / L and stir for 1 h; Weigh 1 g of the dried NaY zeolite powder and add it to the zinc nitrate solution, then stir for 24 h; Wash the mixed solution 3 times with 1 L of deionized water under vacuum filtration, and dry the obtained zeolite in an oven at 110 °C for 4 h to obtain Zn 2+ modified ZnX zeolite powder; S2. Prepare cellulose nanofiber CNF dispersion: Dilute 5 mL of the CNF dispersion stock solution with 95 g of deionized water to 0.05 wt%, and stir at a low speed of 400 rpm for 12 h to obtain the CNF dispersion; S3. Mix ZnX zeolite and CNF dispersion: Add ZnX to the CNF dispersion at a loading amount of 15 wt%, stir for 12 h, then ultrasonically treat for 15 min, and further treat with a high-speed disperser at 8000 rpm for 10 min to form a mixed dispersion; S4. Vacuum filtration to form a film: Take 10 mL of the well-dispersed mixed dispersion and vacuum filter it under a vacuum degree of 100 kPa to form a hydrogel cake. Dry the cake in an oven at 45 °C for 12 h to obtain a ZnX@CNF composite film with a ZnX zeolite loading amount of 15 wt%. The data of CO2 permeability and CO2 / N2 selectivity for Comparative Examples 1 to 8 are listed in Table 2. Table 1 CO2 permeability and CO2 / N2 selectivity indexes for Examples 1 to 16 Table 2 CO2 permeability and CO2 / N2 selectivity indexes for Comparative Examples 1 to 8 Control ratio number Membrane type <![CDATA[CO2 Permeability (Barrer)]]> <![CDATA[CO2 / N2 selectivity]]> Control ratio 1 NaY 33.4 11.5 Control ratio 2 ZnY 48.7 26.6 Control ratio 3 CNF membrane 6.2 7.2 Control ratio 4 15wt%NaY@CNF 139.9 33.5 Control ratio 5 15wt%ZnY@GO 157.2 59.3 Control ratio 6 15wt%KY@CNF 103.5 44.3 Control ratio 7 15wt%AlY@CNF 86.8 32.2 Control ratio 8 15wt%ZnX@CNF 184.8 73.7 Combining the data indexes in Table 1 and Table 2 Figure 11 and Figure 12 It is found that the optimal sample prepared by the method provided by the present invention is the ZnY@CNF composite film with a zeolite loading amount of 15 wt%, the CO2 permeability is 266.7, and the CO2 / N2 selectivity is 92.4, and for Comparative Example 1, the unmodified Y-type zeolite NaY with divalent metal cations, and Comparative Example 2 with Zn 2+Compared with the modified Y-type molecular sieve ZnY and the CNF membrane without any molecular sieve in Comparative Example 3, the CO2 permeability and the selectivity of CO2 / N2 of the optimal sample are significantly higher than those of Comparative Example 1, Comparative Example 2, and Comparative Example 3. The CO2 permeability is increased by 81.7% - 97.7% compared with that of Comparative Example 1, Comparative Example 2, and Comparative Example 3, and the selectivity of CO2 / N2 is increased by 71.2% - 92.2%; compared with the molecular sieve without divalent metal cation modification and the 15wt% NaY@CNF composite membrane with a loading amount in Comparative Example 4, the CO2 permeability and the selectivity of CO2 / N2 of the optimal sample are significantly higher than those of Comparative Example 4. The CO2 permeability is increased by 47.5%, and the selectivity of CO2 / N2 is increased by 63.7%; compared with the 15wt% ZnY@CO composite membrane with a loading amount of 15wt% and composite with graphene oxide of the Y-type molecular sieve modified by divalent cations in Comparative Example 5, the CO2 permeability and the selectivity of CO2 / N2 of the optimal sample are significantly higher than those of Comparative Example 5. The CO2 permeability is increased by 41.1%, and the selectivity of CO2 / N2 is increased by 35.8%; compared with the 15wt% KY@CNF composite membrane with a loading amount of 15wt% of the Y-type molecular sieve modified by monovalent metal cations in Comparative Example 6, the CO2 permeability and the selectivity of CO2 / N2 of the optimal sample are significantly higher than those of Comparative Example 6. The CO2 permeability is increased by 61.2%, and the selectivity of CO2 / N2 is increased by 52.1%; compared with the 15wt% AlY@CNF composite membrane with a loading amount of 15wt% of the Y-type molecular sieve modified by trivalent metal cations in Comparative Example 7, the CO2 permeability and the selectivity of CO2 / N2 of the optimal sample are significantly higher than those of Comparative Example 7. The CO2 permeability is increased by 67.5%, and the selectivity of CO2 / N2 is increased by 65.2%; compared with the 15wt% ZnX@CNF composite membrane with a loading amount of 15wt% of the X-type molecular sieve modified by divalent metal cations in Comparative Example 8, the CO2 permeability and the selectivity of CO2 / N2 of the optimal sample are significantly higher than those of Comparative Example 8. The CO2 permeability is increased by 30.7%, and the selectivity of CO2 / N2 is increased by 20.2%. It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the spirit and scope of the technical solutions of the present invention, and they should all be covered within the scope of the present invention. In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for the description of the embodiments will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts. Figure 1XRD patterns of different divalent metal cation modified Y zeolites and NaY zeolites prepared in the present invention. Compared with the unmodified NaY zeolite, the characteristic diffraction peaks of all modified Y zeolites ZnY, CoY, NiY, and MgY did not change, and the original peaks were retained. The peaks located at 6.2°, 10.1°, 11.9°, 15.6°, and 24.0° are attributed to (111), (220), (311), (331), and (533) of the lattice structure of highly crystalline NaY zeolite, respectively. Figure 2 SEM images of different divalent metal cation modified Y zeolites and NaY zeolites prepared in the present invention. The morphology and particle size analysis were carried out on the divalent metal cation modified Y zeolites ZnY, CoY, NiY, MgY and the unmodified NaY zeolite. Compared with the NaY zeolite, all the divalent metal cation modified zeolites showed similar morphology, with uniform particle distribution and complete crystals, indicating that ion exchange does not cause structural damage or aggregation of the particles. Figure 3 Gas permeability diagrams of NaY@CNF, ZnY@CNF, CoY@CNF, NiY@CNF, MgY@CNF composite membranes and pure CNF membranes with different loadings prepared in the present invention. When the zeolite loading is 5 wt%, the CO2 permeability increases significantly, indicating that the presence of Y zeolite can generate additional gas channels. When the zeolite loading is 20 wt%, the CO2 permeability can reach up to 294.3 Barrer at most, so the CO2 permeability is positively correlated with the zeolite loading. It is worth noting that for all membranes, the gas fluxes of the composite membranes with a loading of 20 wt% and 15 wt% are very close. Figure 4 CO2 / N2 gas selectivity diagrams of NaY@CNF, ZnY@CNF, CoY@CNF, NiY@CNF, MgY@CNF composite membranes and pure CNF membranes with different zeolite loadings prepared in the present invention. As the zeolite ratio increases, the CO2 / N2 selectivity increases, but due to excessive loading, the ideal selectivity of the composite membrane for CO2 / N2 decreases to a certain extent. Combining Figure 3 with the CO2 permeability, it is considered that the performance of the ZnY@CNF composite membrane with a loading of 15 wt% is the best. Figure 5 Gas separation performance diagrams of the ZnY@CNF composite membrane with the best performance prepared in the present invention at different temperatures. As the temperature increases, the thermal motion of gas molecules increases, resulting in enhanced diffusion of molecules between the membrane layers, and the change in N2 is more obvious, which will cause a certain decrease in selectivity to a certain extent. Figure 6Gas separation performance diagram of the ZnY@CNF composite membrane with the optimal performance prepared by the present invention under different pressures. The change in pressure does not significantly affect the separation performance of the composite membrane, which is attributed to the dense structure of the composite membrane, making it less sensitive to pressure changes. Figure 7 XRD patterns of the ZnY@CNF composite membrane with the optimal performance, pure CNF membrane, and ZnY molecular sieve prepared by the present invention. The peaks located at 14.58° and 22.46° confirm that the pure CNF membrane retains the typical cellulose I crystal structure. In the ZnY@CNF composite membrane, ZnY and CNF retain their topological structures. Figure 8 FT-IR curves of the ZnY@CNF composite membrane with the optimal performance, pure CNF membrane, and ZnY molecular sieve prepared by the present invention. The characteristic peaks of the original CNF membrane appear at 3430 cm -1 and 1640 cm -1 and belong to the stretching vibration of -OH; 2980 cm -1 and 1400 cm -1 are the bending vibrations of C-H; the peak at 1050 cm -1 is attributed to the stretching vibration of C-O-C; the high-intensity band located at 1030 cm -1 is attributed to the asymmetric stretching vibration of Si-O-Si inside the Y molecular sieve; the characteristic peaks at 3430 cm -1 and 1640 cm -1 are the proton vibrations of water molecules in the Y-type molecular sieve structure; indicating that the molecular sieve is successfully introduced into CNF. Figure 9 TGA curves of the ZnY@CNF composite membrane with the optimal performance, pure CNF membrane, and ZnY molecular sieve prepared by the present invention. The TGA curves of the pure CNF membrane and the ZnY@CNF composite membrane show a two-stage weight loss trend. The first stage before 120 °C is attributed to the adsorbed water, and the second stage between 200 and 300 °C is attributed to the dissolution of cellulose. Figure 10 CO2 adsorption performance diagrams of the ZnY@CNF composite membrane with the optimal performance and pure CNF membrane prepared by the present invention at 0 °C and 25 °C. At the adsorption temperature of 0 °C, the adsorption capacity shows a good linear relationship with the pressure. The CO2 adsorption capacity increases with the increase in pressure. The maximum adsorption capacity of the pure CNF membrane is 2.5 cm 3 / g STP, while the maximum adsorption capacity of the ZnY@CNF composite membrane is 11.5 cm 3 / g STP, indicating that the addition of zeolite ZnY to the molecular sieve can increase the adsorption of CO2. In addition, the desorption process on the composite membrane is irreversible and stops at 10.4 mmHg. An unclosed loop can be observed, which means that there is chemisorption between CO2 and the ZnY@CNF composite membrane. At the same time, we also tested the adsorption-desorption process at different temperatures of 25 °C. Compared with that at 0 °C, the shape of the adsorption-desorption curve remains unchanged, and the maximum adsorption capacity of CO2 by the ZnY@CNF composite membrane decreases to 7.9 cm 3 / g STP, which is because the adsorption of static CO2 molecules is promoted in a low-temperature environment. However, regardless of the temperature, there is always an unclosed loop in the ZnY@CNF composite membrane, which further illustrates the chemisorption of CO2, probably the π-π* complexation between Zn 2+ and CO2, which promotes the transport of CO2. Figure 11 This is the gas separation and permeation performance diagram of the ZnY@CNF composite membrane, which is the optimal sample prepared in the present invention, and Comparative Examples 1 to 8. The CO2 permeation performance of the ZnY@CNF composite membrane is better than that of all the comparative samples in Comparative Examples 1 to 8, showing significant advantages. Under the same test conditions, the CO2 permeability of the ZnY@CNF composite membrane reaches 266.7 Barrer. Figure 12 This is the gas selectivity performance diagram of the ZnY@CNF composite membrane, which is the optimal sample prepared in the present invention, and Comparative Examples 1 to 8. The CO2 / N2 selectivity of the ZnY@CNF composite membrane is better than that of all the comparative samples in Comparative Examples 1 to 8, showing significant advantages. Under the same test conditions, the CO2 / N2 selectivity of the ZnY@CNF composite membrane reaches 92.4. In summary, the present invention provides an inorganic filler-doped nanocellulose gas separation membrane, its preparation method, and its application in separating CO2 and N2. By combining a Y-type zeolite exchanged with divalent metal cations with cellulose nanofibers and using a vacuum-assisted filtration technique to prepare a composite membrane. This membrane enhances CO2 transport through the π-π* complexation of Zn 2+ and simultaneously synergizes the sieving effect of the zeolite and the solution-diffusion mechanism of cellulose to improve the separation performance, having excellent separation performance, good material compatibility, long-term operation stability, simple process, high mechanical properties, thermal stability, environmental friendliness, etc. Under the optimal conditions, the CO2 permeability reaches 266.7 Barrer, the CO2 / N2 selectivity reaches 92.4, and it remains stable during long-term testing. The present invention provides a low-cost and environmentally friendly membrane material solution for efficient carbon capture and has great potential in the application of carbon capture and separation.
Claims
1. An inorganic filler-doped nanocellulose gas separation membrane, characterized in that: The nanocellulose gas separation membrane uses cellulose nanofibers as a support, and a modified Y-type molecular sieve is loaded on the cellulose nanofiber support. The modified Y-type molecular sieve is a Y-type molecular sieve modified with a divalent metal cation.
2. A method for preparing an inorganic filler-doped nanocellulose gas separation membrane, characterized in that: The method comprises the following steps: S1. Prepare a divalent metal cation-modified Y-type molecular sieve: The vacuum-dried molecular sieve powder and the divalent metal salt solution are fully stirred, and then vacuum filtered, rinsed, and dried to obtain a divalent metal cation-modified Y-type molecular sieve; S2. Preparing a cellulose nanofiber CNF dispersion: diluting the cellulose nanofiber dispersion mother liquid with deionized water and stirring at a low speed to form a CNF dispersion; S3. Mixed CNF dispersion and divalent metal cation-modified Y-type molecular sieve: The divalent metal cation-modified Y-type molecular sieve is added to the CNF dispersion, and after sufficient stirring, the mixed dispersion is formed by ultrasonic and mixed disperser treatment; S4. Vacuum filtration membrane formation: The mixed dispersion is vacuum filtered to form a hydrogel filter cake, which is then dried to obtain a composite membrane.
3. The preparation method according to claim 2, characterized in that: The divalent metal salt solution described in step S1 can be selected from any one or more of zinc salt solution, cobalt salt solution, nickel salt solution, and magnesium salt solution; the concentration of the divalent metal salt solution is 0.1-0.5 mol / L; the mass volume ratio of the Y-type molecular sieve modified with divalent metal cations and the divalent metal salt solution is 0.02-0.25:1 g / mL, and the reaction time is 1-2 days.
4. The preparation method according to claim 3, characterized in that: The zinc salt solution is any one or more of zinc chloride, zinc sulfate, zinc acetate, zinc nitrate, zinc nitrite, zinc phosphate, zinc carbonate, zinc borate, zinc iodide, and zinc bromide; the cobalt salt solution is any one or more of cobalt chloride, cobalt sulfate, cobalt acetate, cobalt nitrate, cobalt carbonate, cobalt iodide, and cobalt bromide; the nickel salt solution is any one or more of nickel chloride, nickel sulfate, nickel nitrate, nickel oxalate, nickel sulfamate, nickel iodide, and nickel bromide; the magnesium salt solution is any one or more of magnesium chloride, magnesium sulfate, magnesium nitrate, magnesium acetate, magnesium bromide, magnesium iodide, and magnesium perchlorate.
5. The preparation method according to claim 2, characterized in that: The drying temperature in step S1 is 100° C. to 200° C., and the drying time is 3 to 5 hours.
6. The preparation method according to claim 2, characterized in that: The concentration of the CNF dispersion in step S2 is 0.01-0.10 wt %, the low-speed stirring rate is 200-500 rpm, and the stirring time is 10-20 h.
7. The preparation method according to claim 2, characterized in that: The addition amount of the divalent metal cation-modified Y-type molecular sieve in step S3 is 5 to 20 wt% of the total mass of the CNF dispersion, the reaction time is 10 to 20 h, the ultrasonic treatment time is 10 to 20 min, the speed of the high-speed disperser is 6000 to 10000 rpm, and the treatment time is 10 to 30 min.
8. The preparation method according to claim 2, characterized in that: The vacuum degree of the vacuum filtration in step S4 is 100 kPa; The drying temperature is 30-60°C and the drying time is 10-20 hours.
9. Use of the divalent metal cation-modified Y-type molecular sieve-doped nanocellulose gas separation membrane as claimed in claim 1 in separating CO2 and N2.